If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -3(x + -5) + 9(y + -5) = 0 Reorder the terms: 5x + -3(-5 + x) + 9(y + -5) = 0 5x + (-5 * -3 + x * -3) + 9(y + -5) = 0 5x + (15 + -3x) + 9(y + -5) = 0 Reorder the terms: 5x + 15 + -3x + 9(-5 + y) = 0 5x + 15 + -3x + (-5 * 9 + y * 9) = 0 5x + 15 + -3x + (-45 + 9y) = 0 Reorder the terms: 15 + -45 + 5x + -3x + 9y = 0 Combine like terms: 15 + -45 = -30 -30 + 5x + -3x + 9y = 0 Combine like terms: 5x + -3x = 2x -30 + 2x + 9y = 0 Solving -30 + 2x + 9y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '30' to each side of the equation. -30 + 2x + 30 + 9y = 0 + 30 Reorder the terms: -30 + 30 + 2x + 9y = 0 + 30 Combine like terms: -30 + 30 = 0 0 + 2x + 9y = 0 + 30 2x + 9y = 0 + 30 Combine like terms: 0 + 30 = 30 2x + 9y = 30 Add '-9y' to each side of the equation. 2x + 9y + -9y = 30 + -9y Combine like terms: 9y + -9y = 0 2x + 0 = 30 + -9y 2x = 30 + -9y Divide each side by '2'. x = 15 + -4.5y Simplifying x = 15 + -4.5y
| x^4-9x+7=0 | | x^4-8x^3+9x^2+28x-60=0 | | -9+n=-2(-3-2n) | | 4m+9=7m+12 | | y^4+2y^2+1=0 | | 2(-5r-6)=-12-6r | | 8x+19=26 | | 4x+2=9-2x | | 4(5x+2)=-24+4x | | 3(k-3)-5=7k-(3k-2) | | f(x)=9xln(7x)-9x | | 2[3-4(5-7)]= | | -3(1r+3)=-1(-6+36) | | (6x+6)(2x^2+4x+4)= | | 9x-12=8x+3 | | -5a-25=5(-2a+4)-4a | | 2cos(x)sin(x)=-sin(x) | | 2m+4n+6m+5n= | | 6.9=9.6 | | y^4-1= | | -6(3p+4)=16+2p | | 3+2(1-3x)=1-2x | | x^10-16= | | 4v=5(v+1) | | X-6=-13/2 | | x^5-80x= | | 1.4x=43.90 | | 7(x+6)=6(x-7)+x | | -83p+7p-5p+5+30= | | -2(3x-2)=4x-16 | | n/9+1=12 | | (4/5)c-8=-36 |